An analysis of the effects of learner-centered software education and required support strategies - Ahn, Seongjin; Oh, Kyungsun (Frontiers in Education, 2024)
This study investigates support strategies to enhance basic software education as a liberal arts course at Konkuk University, South Korea, by integrating design thinking and computational thinking to mitigate the cognitive load of programming.A study with 190 students utilized a learner-centered approach, incorporating design thinking and computational problem-solving, and evaluated its effectiveness through pre-and posttests and structural equation modeling.The intervention successfully reduced the cognitive load associated with programming tasks and led to positive changes in computational thinking factors. Our analysis also revealed that cognitive load negatively impacted all computational thinking factors and that improvements in computational thinking factors were sustained into subsequent stages of the learning process.The findings suggest that as differences in student learning capabilities become more pronounced, a variety of tailored learning strategies must be employed. Software education should incorporate computational thinking factors such as problem decomposition, abstraction, and algorithmic procedures to lower cognitive load. Additionally, it is crucial to foster immersion in learning by implementing attention, relevance, confidence, and achievement strategies.